Epidemiological characterization of Hepatitis A, Casanare-Colombia, 2013-2019 - Aranguren, Sandra (2021)
Introduction: Eradication of viral hepatitis -among them, hepatitis A- is a key part of the strategy towards implementation of environmental sanitation and immunization. Objective. here was to describe hepatitis A epidemiological trends at the department of Casanare during 2013-2019 timespan. Methods: Cross-sectional descriptive study from the compulsory notification of event to Sivigila. Variable analysis with descriptive statistics included in the event's file by person-place-time with Epi-Info® / Microsoft Excel®. Incidence and hospitalization rates were computed by 100.000 inhabitants. Results: 90,5% of cases (152/168) were inhabitants at Casanare; 3,2% of registries (5/152) purged, 6,8% (10/147) discarded y 90,1% (137/147) required analysis; 63,2% (12/19) of municipalities reported cases. Annual average of cases: 19,6±22,7 (r=4, 2017 – 70, 2019). By place/sex: urban 75 (54,7%) men, male/female ratio=1:0,8; mean age=19,3 yr ±13,1 (r=0,7-69,0); 53 (38,7%) in 10-19 yr-old group. By Incidence Rate: general population=5,4; men=5,8; women=5,0; y 10,4 in 10-19 yr-old group. Average TH=6,9/100.000, all alive. Discussion: The year 2019 concentrated almost half the reported cases within the study period, similarly to the whole country. It is recommended to keep on surveillance not just on quality of water or the event itself, but to carry on the community education about measures for personal hygiene, food safety and vaccination coverage against hepatitis A.